RESEARCH OF DYNAMICS AND FORECASTING THE BUDGET INCOMES FROM EXCISE TAXATION: THE UKRAINE EXPERIENCE - Liubov Lysiak; Oksana Grabchuk; Svitlana Kachula; Hlib Shchyryi (Фінансово-кредитна діяльність: проблеми теорії та практики, 2022)
The purpose of the article is to determine the priority methods of forecasting the number of tax revenues from excise taxation as a source of formation of budgetary resources, taking into account the patterns of their dynamics. A methodical approach of determining the general patterns of the dynamics of the number of tax revenues from the collection of excise taxes to the budget of Ukraine has been developed. On the basis of this approach, it was established that the formalized description of the patterns of dynamics of tax revenues from the collection of excise taxes to the budget of Ukraine has significant differences depending on the scale of measurements. The usage of time series to forecast the number of tax revenues from the collection of excise taxes is also not appropriate due to their anti-persistence and fractal similarity. The study of the uncertainty of the dynamics of tax revenues from the collection of excise taxes makes it possible to predict the onset of periods of crisis reduction, with high convergence of results, regardless of the scale of measurement. Parametric forecasting of the number of tax revenues from the excise tax to the budget of Ukraine is carried out by taking into account the inertia of the dynamics of factors of influence, confirmation of causality between factors of influence, factors of influence and forecast indicators, determination of lag of causality, research of persistence of dynamics of the factors of influence. Due to the anti-persistence of the dynamics of some of the factors of influence, the forecasting of the number of tax revenues from the collection of excise tax was carried out using a set of parametric and scenario models. The results of forecasting the number of tax revenues from the excise tax on goods produced in Ukraine were lower than the official forecast by 10-12%. The results of forecasting the number of tax revenues from the collection of excise tax on goods imported to the territory of Ukraine coincided with the official forecast.